2022
DOI: 10.1002/advs.202104588
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously Achieving Highly Efficient and Stable Polymer:Non‐Fullerene Solar Cells Enabled By Molecular Structure Optimization and Surface Passivation

Abstract: Dedicated to Professor Baowen Zhang on the occasion of her 80th birthday. Despite the tremendous efforts in developing non-fullerene acceptor (NFA) for polymer solar cells (PSCs), only few researches are done on studying the NFA molecular structure dependent stability of PSCs, and long-term stable PSCs are only reported for the cells with low efficiency. Herein, the authors compare the stability of inverted PM6:NFA solar cells using ITIC, IT-4F, Y6, and N3 as the NFA, and a decay rate order of IT-4F > Y6 ≈ N3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 57 publications
1
24
1
Order By: Relevance
“…[22][23][24] Furthermore, the fundamental identification of photodegradation pathways for BTP-series NFAs is considerably lagging behind their related efficiency thriving. 22,25 Hence, tremendous efforts to reduce the large discrepancy between efficiency and photostability are urgently needed for the further development of OPVs.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Furthermore, the fundamental identification of photodegradation pathways for BTP-series NFAs is considerably lagging behind their related efficiency thriving. 22,25 Hence, tremendous efforts to reduce the large discrepancy between efficiency and photostability are urgently needed for the further development of OPVs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the composite electron transport layer, both the efficiency and stability of target OSCs have exhibited noticeable enhancement. 16–19 For example, Zhou et al reported that aqueous polyethylenimine (a-PEI) modification on the ZnO surface simultaneously enhanced the efficiency and stability of nonfullerene organic solar cells. 19 The device efficiency was improved from 15.2% for the ZnO ETL to 15.7% for the device based on a-PEI-modified ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to photo-oxidation, all those NFAs undergo strong absorption degradation when their NFAs/ZnO films are illuminated either in ambient or in inert condition, while increasing the side-chain lengths on either the inner pyrrole or the outer thiophene rings result in enhanced degradation (Figure 2d-f). Regards to the previous work where the substitution of end-group in NFAs can alter the electron cloud density of CC linkage between "A" and "D" units in ITIC acceptor and further affect its chemical stability, [28][29][30] we infer that the reason behind the different photochemical stabilities in our Y6 family NFAs is also due to the effect of the side chain length on the electron cloud distribution in NFA structures -the increased side chain length on either the inner pyrrole or the outer thiophene rings in NFA structure can enhance the electron cloud density of CC linkage between "A" and "D" units and make it easier to break, leading to reduced photochemical stability. As such, we believe that further alky chain modification in A-D-A and A-DA'D-A structured NFAs can be 3d.…”
Section: Resultsmentioning
confidence: 99%